Effectiveness of an Opt-Out Electronic Heath Record-Based Tobacco Treatment Consult Service at an Urban Safety Net Hospital - Herbst, Nicole; Wiener, Renda Soylemez; Helm, Eric D; O'Donnell, Charles; Fitzgerald, Carmel; Wong, Carolina; Bulekova, Katia; Waite, Meg; Mishuris, Rebecca G; Kathuria, Hasmeena (Chest, 2020)
To address the burden of tobacco use in underserved populations, our safety net hospital developed a tobacco treatment intervention consisting of an "opt-out" electronic health record-based best practice alert + order set, which triggers consultation to an inpatient tobacco treatment consult (TTC) service for all hospitalized smokers. We sought to understand if the intervention would increase patient-level outcomes (receipt of tobacco treatment during hospitalization and at discharge; 6-month smoking abstinence) and improve hospital-wide performance on tobacco treatment metrics. We conducted two retrospective quasi-experimental analyses to examine effectiveness of the TTC service. Using a pragmatic design and multivariable logistic regression, we compared patient-level outcomes of receipt of nicotine replacement therapy and 6-month quit rates between smokers seen by the service (n = 505) and eligible smokers not seen because of time constraints (n = 680) between July 2016 and December 2016. In addition, we conducted an interrupted time series analysis to examine the effect of the TTC service on hospital-level performance measures, comparing reported Joint Commission measure rates for inpatient (Tob-2) and postdischarge (Tob-3) tobacco treatment preimplementation (January 2015-June 2016) vs postimplementation (July 2016-December 2017) of the intervention. Compared with inpatient smokers not seen by the TTC service, smokers seen by the TTC service had higher odds of receiving nicotine replacement during hospitalization (260 of 505 [51.5%] vs 244 of 680 [35.9%]; adjusted ORs [AOR], 1.93 [95% CI, 1.5-2.45]) and at discharge (164 of 505 [32.5%] vs 84 of 680 [12.4%]; AOR, 3.41 [95% CI, 2.54-4.61]), as well as higher odds of 6-month smoking abstinence (75 of 505 [14.9%] vs 68 of 680 [10%]; AOR, 1.48 [95% CI, 1.03-2.12]). Hospital-wide, the intervention was associated with a change in slope trends for Tob-3 (P < .01), but not for Tob-2. The "opt-out" electronic health record-based TTC service at our large safety net hospital was effective at improving both patient-level outcomes and hospital-level performance metrics, and could be implemented at other safety net hospitals that care for hard-to-reach smokers.